Phytosociological study of herbaceous communities under Vachellia tortilis subsp. raddiana (Savi) Kyal. & Boatwr in eastern Niger - Ismael Bio; Mamadou Boubacar Moussa; Idrissa Soumana; Ali Mahamane (Journal of Agriculture and Environment for International Development)
The present study was conducted in eastern Niger with the objective of assessing the floristic diversity under the canopy of Vachellia tortilis. To collect detailed data on the plant species present, the sigmatist method of abundance-dominance of Braun-Blanquet was employed, which is a common phytosociological technique for determining the relative abundance and dominance of species in each area. This method helps classify species based on their frequency and coverage. A total of 138 plots were surveyed to ensure a comprehensive representation of the study area. These plots were distributed across various locations under the canopy of V. tortilis, covering diverse topographies and environmental conditions. Hierarchical Ascending Classification (HAC) was used to group plant species based on their similarities in abundance and presence across the plots. Detrended Correspondence Analysis (DCA) helped visualize the distribution of plant species in relation to environmental gradients such as soil type and moisture content, ensuring that plant groupings were not solely influenced by environmental variables. Canonical Correspondence Analysis (CCA) was employed to further explore the relationships between plant species and environmental factors, providing a deeper understanding of how plant communities are structured and influenced by both biotic and abiotic factors. The results revealed 5 plant groupings with a total species richness of 35 herbaceous species divided into 19 families. The analysis of the floristic composition shows that the Poaceae family (41.08%) is the most important, followed by the Mimosaceae (14.82%). The analysis of diversity indices shows that the greatest specific diversity is observed in the V. tortilis and Cenchrus biflorus grouping (22 species) with a Shannon index of 2.96 and a Piélou equitability of 0.83. The dominance of Poaceae under the V. tortilis canopy suggests that this tree species influences herbaceous community composition by creating favorable ecological conditions such as soil moisture retention and light availability.